Effect of household socioeconomic status on household dyanamics in a high HIV prevalence area of the KwaZulu-Natal province from 2003 - 2012 - Gweliwo, Patricia (My University, 2016)
Socio-economic status (SES) disparities do not only exist between racial groups in South Africa but also exists within the vulnerable black population with the devastating impacts of the HIV epidemic. Households are important determinants of human welfare. However, little is known about the effect of household socio-economic status on the establishment and break-up of households within a low-resource setting and a severe HIV epidemic. It is in the midst of these challenges in rural South Africa that this study examined the effect of household SES on household formation and dissolution among the black population in rural northern KwaZulu-Natal. METHODS Using longitudinal data from the period 2003-2012 from the Africa Centre for Health and Population Studies, the study used a cross-sectional study design approach to examine the effect of household SES on household formation. It also examined the effect of household SES change (i.e. either positive, negative change or stable SES) between the start and end of observation of a household within the study period. Household formation was defined as when an individual or individuals come from different households to form a new social unit with a new household head. Dissolution occurred when all individuals in a household end their membership to a household due to death, out-migration or by joining other households. Separate regression models for the two outcomes, household formation and dissolution were explored with household SES covariates while adjusting for other household variables. RESULTS Household formation and dissolution trends both decreased over the study period. Out of a total of 18,249 households, newly formed households had a relatively higher percentage of tertiary educated household heads (10.7% versus 2.5%), unemployed household members (41.6% versus 28.5%), grant recipient household members (37.1% versus 8.5 %) and households within the average to richest wealth quintiles (44.1% versus 36.4 %) than pre-existing households. Multivariate analysis showed that tertiary educated household heads (aOR=2.96, 95% (CI) 2.26-3.89) and households within the average to richest wealth quintiles most especially the 4th quintile (aOR=3.29, 95% (CI) 2.69-4.04) were associated with a higher odds of households being newly formed. However, the lesser the employed members (aOR=0.31, 95% (CI) 0.21-0.45) and grant recipients per household size in a household (aOR=0.15, 95% (CI) 0.12-0.18) the lower the odds of formation. Furthermore, small size households (aOR=0.68, 95% (CI) 0.56-0.80) and unmarried household heads (aOR =0.47, 95% (CI) 0.40-0.55) were associated with lower odds of being newly formed. Whereas female headed households (aOR=2.23, 95% (CI) 1.93-2.57) were associated with a higher odds of household formation. With regards to household dissolution, close to a quarter of households had an increase in SES over the study period compared to households with a decreased SES (24.6% versus 8.6 %). Similar to household formation, male headed households dominated the study population with the highest proportion in dissolved households (63.8% and 61.5% at start and end of household observation respectively). Also unmarried household heads were the majority in dissolved households (62.7% and 64.1% at start and end of household observation respectively). Approximately 65.6% of households that never dissolved had an extended family type of composition compared to 36.6% of dissolved households. The area was predominantly rural with about 47.2% households in rural segment of the study area. The study has shown that households had lower odds of dissolving if there is a positive change (i.e. an increase) in household SES compared with households with an unchanged SES over the period. In exact terms, an increment in the number of employed household members over the study period was associated 49% lower odds of a household being a dissolved (aOR=0.51 95% (CI) 0.42-0.61). Also, an increment in the number of household grant recipients over the period of observation was associated with a 69% lower odds to result in the dissolution (aOR=0.31 95% (CI) 0.25-0.39). Households with an improved wealth index over the period of study were associated with 55% lower odds of dissolution (aOR =0.45, 95% (CI) 0.38-0.54). However, households with both male and female death (multiple sex) were more likely to dissolve. Similarly, peri-urban (aOR=0.71; 95% (CI) 0.58-0.86) households were more likely to dissolve compared to urban households. Surprisingly divorced, widowed and separated couples were not significantly associated with household dissolution. CONCLUSION SES is an important determinant of household existence and stability. This study has shown a complex relationship between household SES and household formation. Although education and improved household wealth index were more likely to result in household formation, an increase in the number of employed household members and household grant recipients did not necessary have an effect on household formation. Government cash transfers, education, employment of household members are valuable cushioning mechanisms necessary for household stability. There is need for government and non-governmental organisations to set up interventions to improve the socio-economic conditions of poor households prioritising rural and female headed households. This is especially critical in a high HIV prevalence area where these interventions will also mitigate against the burden of the HIV epidemic on the population.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in the Field of Population-Based Field Epidemiology
Keywords: HIV; Socioeconomic Factors